2012
DOI: 10.4142/jvs.2012.13.2.193
|View full text |Cite
|
Sign up to set email alerts
|

A modified method for inducing periodontitis in dogs using a silk-wire twisted ligature

Abstract: This study was designed to assess the effectiveness of a modified silk ligature twisted with wire for inducing advanced periodontitis. Periodontitis was induced in five premolars and one molar of 20 healthy dogs over a 60-day period. The dogs were divided into four groups according to the ligatureinducing materials used: soft moistened food only, wire ligature (WL), silk ligature (SL) and twisted ligature with silk and wire (SWL). Periodontal indices were recorded, and dental radiographs were taken before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
2
9
0
1
Order By: Relevance
“…In current study we used cotton ligature in subgingival area around the neck of dogs premolar teeth to induce chronic periodontitis. This method was in agreement with Kim et al, 2012 andGab Allah et al, 2014 who found that, four weeks after ligature, there was severe destruction of DGJ, periodontal tissues and resorption of both; root and alveolar bone. In addition, gingival inflammation and apical migration of attachment epithelium along the affected root surface were reported [24,25] .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In current study we used cotton ligature in subgingival area around the neck of dogs premolar teeth to induce chronic periodontitis. This method was in agreement with Kim et al, 2012 andGab Allah et al, 2014 who found that, four weeks after ligature, there was severe destruction of DGJ, periodontal tissues and resorption of both; root and alveolar bone. In addition, gingival inflammation and apical migration of attachment epithelium along the affected root surface were reported [24,25] .…”
Section: Discussionsupporting
confidence: 78%
“…This method was in agreement with Kim et al, 2012 andGab Allah et al, 2014 who found that, four weeks after ligature, there was severe destruction of DGJ, periodontal tissues and resorption of both; root and alveolar bone. In addition, gingival inflammation and apical migration of attachment epithelium along the affected root surface were reported [24,25] . The DGJ of dogs with induced chronic periodontitis revealed intense OPN extra cellular expression by epithelial cells of hyperplastic gingival layers except the cornfield one which had a negative reaction.…”
Section: Discussionsupporting
confidence: 78%
“…Ligature-induced periodontitis model in beagle dogs was made as previously described._ENREF_32 [36] Briefly, two weeks after scaling, dogs were anesthetized by i.v. injection of pentobarbital sodium (30 mg/kg), and then dental ligature wires (Class One Orthodontics, USA) were tied around the cervical region of the left upper second premolar (PM2), third premolar (PM3), and fourth premolar (PM4) as well as the left lower PM3, PM4, and first molar (PM1) to induce periodontitis.…”
Section: Pharmacokinetics Studymentioning
confidence: 99%
“…The ligature was left in place for 14 days as a gingival irritant and resulted in the development of plaque and periodontitis. The animals were kept in a uniform environment for 14 days and were checked daily to evaluate the suture, food and water intake, and body weight [15,16].…”
Section: Assessment Of In Vivo Anti-periodontitis Activitymentioning
confidence: 99%